Penampilan Karakter Morfologi dan Fisiologi Tiga Kelapa Hibrida Kopyor dan Tetuanya [Performance Of Morphology And Physiology Characters Of Three Coconut Hybrids Of Kopyor and Its Parent] - M Nur; Jeanne Palit; Putri Wulan Adiningrum; Djuito Lumintang; nFN Miftahorrachman (Buletin Palma, 2020)
Morphological and physiological characters are indicator parameters in plants to determine whether plants have good growth or vice versa. This study aims to determine the morphological and physiological characters of the three kopyor hybrid coconuts with three female parents. The study was designed in a Randomized Block Design consisting of six treatments, namely GKK x DKS, GHK x DKS, and GCK x DKS hybrid coconuts as well as three female parents namely Kopyor Yellow Dwarf (GKK) open pollination, Kopyor Green Dwarf (GHK) open pollination, and Kopyor Brown Dwarf (GCK) open pollination. The replication was three times and each experimental unit consisted of 15 plants. Morphological parameters observed included stem length, girth of stem, number of leaves, leaf length, number of leaflets, length of leaflets, leaflet width, and length of the petiole. Phisiological parameters consist of chlorophyll a, chlorophyll b, total chlorophyll and stomata density. The results of analysis of variance and HSD follow-up tests showed different morphological characters were girth of stem (LB) between the treatment of GKK x DKS and the treatment of GHK x DKS, GCK x DKS, and Kopyor Yellow dwarf open pollination; number of leaves (JD) between GKK x DKS and GCK x DKS, Kopyor Green Dwarf open pollination, and Kopyor Brown Dwarf open pollination treatments; leaf length (PD) between GKK x DKS treatment and GCK x DKS and Kopyor Green Dwarf treatments; the number of leaflets (JAD) between the Kopyor Green Dwarf open pollination and GKK x DKS, Kopyor Brown Dwarf open pollination, and Kopyor Green Dwarf open pollination treatments. The difference ofphysiological characters are chlorophyll b between the GKK x DKS treatment and the GHK x DKS, GCK x DKS, and Kopyor Green Dwarf open pollination treatments; total chlorophyll between GKK x DKS treatment with GHK x DKS, GCK x DKS, Kopyor Green Dwarf open pollination, and Kopyor Brown Dwarf open pollination treatments. The average of the 12 parameters observed, the GHK x DKS treatment was the most vigorous among the treatments, while the weakest was the GKK x DKS treatment and its parent Kopyor Yellow Dwarf open pollination.ABSTRAKKarakter morfologi dan fisiologi merupakan parameter indikator pada tanaman untuk mengetahui apakah tanaman memiliki pertumbuhan yang baik atau sebaliknya.Penelitian ini bertujuan untuk mengetahui keragaan karakter morfologi dan fisiologi tiga kelapa hibrida kopyor dengan tiga tetua betinanya.Penelitian dirancang dalam Rancangan Acak Kelompok terdiri dari enam perlakuan, yaitu kelapa hibrida GKK x DKS, GHK x DKS, dan GCK x DKS; serta tiga tetua betinanya yaitu Genjah Kuning Kopyor (GKK) penyerbukan terbuka, Genjah Hijau Kopyor (GHK) penyerbukan terbuka, dan Genjah Cokelat Kopyor (GCK) penyerbukan terbuka. Penelitian diulang sebanyak tiga kali dan setiap unit percobaan terdiri dari 15  tanaman. Parameter morfologi yang diamati meliputi panjang batang, lingkar batang, jumlah daun, panjang daun, jumlah anak daun, panjang anak daun, lebar anak daun, dan panjang petiole. Paramater fisiologi terdiri dari kandungan klorofil a, klorofil b, klorofil total dan kepadatan stomata. Hasil analisis sidik ragam dan uji lanjut HSD menunjukkan karakter morfologi yang berbeda adalah lingkar batang (LB) antara perlakuan GKK x DKS dengan perlakuan GHK x DKS, GCK x DKS, dan GKK penyerbukan terbuka; jumlah daun (JD) antara perlakuan GKK x DKS dengan perlakuan GCK x DKS, GHK penyerbukan terbuka, dan GCK penyerbukan terbuka; panjang daun (PD) antara perlakuan GKK x DKS dengan perlakuan GCK x DKS dan GHK penyerbukan terbuka; jumlah anak daun (JAD) antara perlakuan GHK penyerbukanterbuka dengan perlakuan GKK x DKS, GCK penyerbukan terbuka, dan GKK penyerbukan terbuka.Karakter fisiologi yang berbeda adalah klorofil b antara perlakuan GKK x DKS dengan perlakuan GHK x DKS, GCK x DKS, dan GHK penyerbukan terbuka; klorofil total antara perlakuan GKK x DKS dengan perlakuan GHK x DKS, GCK x DKS, GHK penyerbukan terbuka, dan GCK penyerbukan terbuka. Rata-rata 12 parameter yang diamati, perlakuan GHK x DKS paling vigor diantara perlakuan, sedangkan paling lemah vigoritasnya perlakuan GKK x DKS dan tetuanya GKK penyerbukan terbuka. Hasil penelitian diharapkan bisa  memberipilihanantara hibrida kopyor hasil silangan antara GHK x DKS atau GCK x DKS bagi pengembang tipe kelapa hibrida kopyor yang akan digunakan